The general of the precondition of success of physical training of students of special medical group. - Babenko V.G; Evdokimova L.G; Tupitsa J.I; Hapsalis G.L (Kharkov National Pedagogical University, 2011)
The system of physical education of students is considered. Health influence of the organized forms of employments is rotined by physical exercises on the organism of students. The conceptual going opens up near the mechanism of functioning of the system of physical education under various conditions of activity. It is set that the existent systems of strengthening of health and maintenance of the proper physical standards have close intercommunication. They depend on the preliminary formed positive motivation of students to perfection and self-perfection of physical culture and sport facilities. It is recommended to conduct employments in the close co-operating with other educational disciplines under the direction of experimental specialists of medicine and physical education.